Mädchen auf dem Weg ins Erwerbsleben: Wünsche, Werte, Berufsbilder Forschungsergebnisse zum Girls'Day - Mädchen-Zukunftstag 2013 - Funk, Lore (Verlag Barbara Budrich, 2014)
What do girls want from their future profession? What image do STM professions have in the eyes of girls? What do companies and institutions need to take into account when designing career guidance programmes for girls? The authors deal with these and other questions on gender-specific career guidance on the basis of evaluation results for Girls' Day 2013.